VALUATION AND PROPOSED SOLUTION OF DIGITAL BANK ABC - Kun Syah Pradana, Anri
Digital banking companies have changed the face of the industry by providing better services and products in sectors ranging from payments, funding, and lending. Digital banking appears to be able to deliver more competitive, flexible, and additional financial services and products at lower costs by utilizing in-depth and comprehensive understanding of the consumer. The incumbents cannot ignore the disruption. They must find and implement strategies in order to keep up with the changes while also taking advantage of and benefit from these condition. ABC officially acquired Bank XYZ to becoming Digital bank ABC after obtaining approval from the OJK, and the acquisition deed was signed by both parties. Unmitigated, ABC poured funds IDR 988.04 billion, to take over all of the shares of Bank XYZ from the previous owner. After the acquisition deed was signed, ABC controlled 99.99% of Bank XYZ shares, while 0.01% was owned by PT ABC Finance. The acquisition of Bank XYZ is driven by the need for ABC to have a digital banking to be more flexible in serving customers. For the research, conventional bank has facing disruption in technology revolution, so bank should changing into digital banking system to able provide needs services activities and easier collaboration, also increase market share, so ABC can compete with other competitor. From calculations using Residual Income, the value of Digital Bank ABC is 1,037,899 million. The higher the value, the faster the company will grow. Residual Income is useful for determining a company's genuine profitability. It suggests that the company's growth will be consistent and it can be forecasted by the change in the worth of the company from year to year. For recommendations on adding new services and product quality, searching for new target areas, and financial aspects, Digital Bank ABC must achieve revenue growth as projected. However, for promotion and organizational culture, Digital Bank ABC must make efficient use of ABC's supporting channels and costs. As a result, the value of Digital Bank ABC will rise.